2003
DOI: 10.1590/s1516-31802003000600004
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus viral load in predicting high-grade CIN in women with cervical smears showing only atypical squamous cells or low-grade squamous intraepithelial lesion

Abstract: The viral load of high-risk HPV types was significantly associated with the diagnosis of CIN2 or CIN3 in women referred because of atypical squamous cells and LSIL abnormalities in their cervical smear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 29 publications
3
19
0
10
Order By: Relevance
“…[13][14][15][16][17][18] The presence of high-risk HPV viral load may also be important in predicting highgrade CIN among women with atypical squamous cells or LSIL in their cervical smears. 19 In the presence of high-risk HPV subtypes, cytological abnormalities may be present in up to 44% of HIV-infected women. 20 In the present study, the HIV-infected women had their first sexual intercourse at an earlier age, a higher number of sexual partners and a higher prevalence of STDs.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] The presence of high-risk HPV viral load may also be important in predicting highgrade CIN among women with atypical squamous cells or LSIL in their cervical smears. 19 In the presence of high-risk HPV subtypes, cytological abnormalities may be present in up to 44% of HIV-infected women. 20 In the present study, the HIV-infected women had their first sexual intercourse at an earlier age, a higher number of sexual partners and a higher prevalence of STDs.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 9.1% of the reagent patients to HPV DNA had cytological diagnosis of ASCUS and 38.1% had NILM (Table 1). In other reports the rate referred to HPV DNA by HCII was 16% in women with ASCUS cytology and 29.6% in women with normal smears (2,11) .…”
Section: Discussionmentioning
confidence: 78%
“…Deve ser tomado cuidado com a possibilidade de quadros de latência levarem a falsos positivos e, portanto, sobrediagnóstico. A possibilidade de diferença entre a carga viral e o diagnóstico da lesão tem sido estabelecida em vários estudos 6,7,8,10,12,13,15,18,22 , embora contestados por outros 23,24 . De fato, o "cutoff" que permite uma melhor performance do teste no diagnóstico de HSIL tem sido bastante variável.…”
Section: Discussionunclassified
“…Assim, hoje se sabe que o tipo 16 é o mais prevalente em todo o mundo 1 , independentemente da gravidade da lesão escamosa, e, de maneira geral, os HPV identificados como de alto risco estão presentes em mulheres imunocompetentes em cerca de 20% dos quadros histológicos negativos, em 70% dosUNIOR UNIOR*, P *, P *, P *, P *, PAULO AULO AULO AULO AULO C C C C CÉSAR ÉSAR ÉSAR ÉSAR ÉSAR G G G G GIRALDO IRALDO Vários pesquisadores defendem a idéia de que a alta carga viral de HPV de alto risco teria uma importante relação com lesões intraepiteliais escamosas e sua maior gravidade 6,7,8,10,12,15,18,22 . Outros pesquisadores enfatizam a importância da persistência da alta carga viral por longo tempo, e não simplesmente uma medida isolada, assim como só teria valor a alta carga viral do HPV tipo 16, sem considerar os demais tipos 2,3,9,13,14,16,17 .…”
Section: Introductionunclassified
See 1 more Smart Citation